2023
DOI: 10.3390/ijerph20020937
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Drug Utilization in Patients with Rare Diseases in Tuscany, Italy: A Population-Based Study

Abstract: Patients with rare diseases (RDs) generally have delayed diagnosis and misdiagnosis, which lead to inappropriate care or the need to modify treatment during the course of the disease. The medical care of RD patients can be further complicated by the presence of comorbidities. In this population-based study, we evaluated the prevalence, intensity of use, and consumption of drugs prescribed to RD patients residing in Tuscany (Italy) in the years 2008–2018. Data from the Registry of Rare Diseases of Tuscany were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…An Italian study investigating medication habits in people with amyotrophic lateral sclerosis (ALS) highlighted patients over 65 years old used more concomitant drugs and had more relevant drug-drug interactions than younger patients, with a worse quality of life [43]. Another population-based study carried out in the Tuscany region, Italy, showed that people aged 80-84 years with RDs had drug consumption three times higher than older people in the general population [44]. Further studies are needed in the monitored population to investigate the real impact of RD-related treatments vs treatments for common comorbidities, as polypharmacy can have peculiar consequences in the RD elderly population [45].…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study investigating medication habits in people with amyotrophic lateral sclerosis (ALS) highlighted patients over 65 years old used more concomitant drugs and had more relevant drug-drug interactions than younger patients, with a worse quality of life [43]. Another population-based study carried out in the Tuscany region, Italy, showed that people aged 80-84 years with RDs had drug consumption three times higher than older people in the general population [44]. Further studies are needed in the monitored population to investigate the real impact of RD-related treatments vs treatments for common comorbidities, as polypharmacy can have peculiar consequences in the RD elderly population [45].…”
Section: Discussionmentioning
confidence: 99%